A representação ético-estética do corpo na fotografia contemporânea - Pozza, Gustavo Luiz (My University, 2016)
Having as objective the understanding of the relationship between ethics and aesthetics in photography, more specifically regarding the representation of the body, this research seeks to understand the process of signification of the image. Due to its indexical characteristic as an image generated by a mechanical process, and so singular in the visual representations, the photographic image stands out with respect to its representation of visually coded reality. Applying methodologies of different authors in the evaluation and analysis of ethical discourse and aesthetic construction, were combined two ways of perception of the image, producing its own methodology, directed to the discussion of the conflicts caused by the representation of immoral as beautiful. Through the understanding of the mechanisms of visual communication by the theories of Peirce, Bazin, Barthes, Sontag e Dubois; the relations between art and ethics from Keiran and Gaut; of studies on the phenomenological and analytical aesthetic and research of methodologies and its application to evaluation of photographic images produced since the early twentieth century, it was possible to obtain relevant data for the analysis of formal construction and moral positioning of the resulting work. This approach has resulted in the proposal of a methodology of ethical and aesthetic evaluation that allows the spectator to understand, analyze and evaluate the photographic work of art.
Objetivando a compreensão das relações entre a ética e a estética na fotografia, mais propriamente com relação à representação do corpo, procura-se compreender o processo de significação da imagem. Devido à característica indicial da imagem gerada por um processo mecânico e por isso singular nas representações visuais, a fotografia se destaca com relação a sua representação da realidade codificada visualmente. Aplicando metodologias de diferentes autores na avaliação e análise do discurso ético e da construção estética, foram combinadas duas possibilidades de percepção da imagem, produzindo uma metodologia própria e direcionada para a discussão dos conflitos causados pela representação do imoral como belo.A partir da compreensão dos mecanismos da comunicação visual pelas teorias de Peirce, Bazin, Barthes, Sontag e Dubois; das relações entre a arte e a ética de Keiran e Gaut; de estudos sobre as estéticas fenomenológica e analítica e da pesquisa de metodologias e da aplicação em avaliações de imagens fotográficas produzidas a partir do início do século XX, foi possível obter dados relevantes para a análise da construção formal e do posicionamento moral da obra resultante. Esse enfoque teve como resultado a proposta de uma metodologia de avaliação ético-estética que permita ao espectador compreender, analisar e avaliar a obra de arte fotográfica.
Keywords: Arte - Filosofia; Estética; Ética; Fotografia; Art - Philosophy; Aesthetics; Ethics; Photographs